Under-Damped System (​ξ < 1)

Watch video

Fig_1_under-damped-system Fig-1

Underdamped system  (ξ<1)\ (\xi < 1)

If the damping factor  ξ\ \xi is less than one or the damping coefficient cc is less than critical damping coefficient ccc_c, then the system is said to be an under-damped system.

ξ<1ORccc<1    c<cc\xi < 1 \quad \text OR \quad {c \over c_c} < 1\implies c < c_c
  • We know that roots of differential equations are:
S1=[ξ+ξ21]ωnS2=[ξξ21]ωnS_1 = \big [-\xi + \sqrt{\xi^2 -1} \big] \omega_n \\ S_2 = \big [-\xi - \sqrt{\xi^2 -1} \big] \omega_n

  • But for  ξ<1\ \xi < 1; the roots for under-damped system are given by S1S_1 and S2S_2 as below:
S1=[ξ+i(1ξ2)]ωnS2=[ξi(1ξ2)]ωn\begin{aligned} S_1 = & \big [-\xi + i \sqrt{(1 - \xi^2)}] \omega_n \\ S_2 = & \big [-\xi - i \sqrt{(1 - \xi^2)}] \omega_n \\ \end{aligned}

Where i=1i = \sqrt{-1} is the imaginary unit of complex root

  • The roots are complex and negative, so the solution of differential equation is given by
x=AeS1t+BeS2tx=Ae[ξ+i(1ξ2)]ωnt+Be[ξi(1ξ2)]ωntx=A.eξωnt.ei(1ξ2)ωnt+B.eξωnt.ei(1ξ2)ωntx=eξωnt[A.ei(1ξ2)ωnt+B.ei(1ξ2)ωnt]x=eξωnt[A.eiωdt+B.eiωdt][(1ξ2)ωn=ωd]\begin{aligned} x &= Ae^{S_1t} + Be^{S_2t} \\ \therefore x &= Ae^{[-\xi + i \sqrt{(1 - \xi^2)}] \omega_nt} + Be^{[-\xi - i \sqrt{(1 - \xi^2)}] \omega_nt} \\ \therefore x &= A.e^{-\xi\omega_nt}.e^{i \sqrt{(1 - \xi^2)} \omega_nt} + B.e^{-\xi\omega_nt}.e^{- i \sqrt{(1 - \xi^2)} \omega_nt} \\ \therefore x &= e^{-\xi\omega_nt} \big [A.e^{i \sqrt{(1 - \xi^2)} \omega_nt} + B.e^{- i \sqrt{(1 - \xi^2)} \omega_nt}] \\ \therefore x &= e^{-\xi\omega_nt} \big [A.e^{i\omega_dt} + B.e^{- i\omega_dt}] \quad \big [ \because \sqrt {(1 - \xi^2) \omega_n} = \omega_d] \end{aligned}
  • According to Euler’s theorem, above equation can be written as:
x=Xeξωnt[sin(ωdt+)]Where  Xand   are constantsx = Xe^{-\xi \omega_nt} \big [\sin (\omega_dt + \varnothing)] \\ \text Where \ \ X \text and \ \ \varnothing \text { are constants}
  • Above equation shows the equation of motion for an underdamped system, and the amplitude reduces gradually and finally becomes zero after some time.

  • Amplitude decreases by  X.eξωnt\ X.e^{-\xi \omega_nt}

  • The natural angular frequency of damped free vibrations is given by:

ωd=(1ξ2)ωn\omega_d = \sqrt {(1 - \xi^2)}\omega_n
  • Time period for under-damped vibration is given by:
tp=2πωd=2π(1ξ2)ωnsec.t_p = {2\pi \over \omega_d} = {2\pi \over \sqrt{(1 - \xi^2)}\omega_n} sec.


Sign in with google to add a comment
By signing in you agree to Privacy Policy

All comments that you add will await moderation. We'll publish all comments that are topic related, and adhere to our Code of Conduct.

Want to tell us something privately? Contact Us

See comments